IMPLEMENTASI PROSES PEMBELAJARAN BERBASIS KURIKULUM 2013 DI SEKOLAH DASAR NEGERI 014 SUNGAI BARU KECAMATAN GAUNG - Erdawati, Sri; Andryco , Andryco (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2022)
This study aims to find out how the implementation of the 2013 Curriculum-based learning process in grades IV, V, and VI at 014 Sungai Baru State Elementary School, Gaung District. This type of research is qualitative research. The sample in this study was 3 class teachers at State Elementary School 014 Sungai Baru, Gaung District. The data in this study were collected using observation, interview and documentation techniques. Furthermore, the collected data was analyzed using the percentage formula. The results of data analysis through observation and interviews can be concluded as follows: The implementation of the 2013 Curriculum-based learning process at 014 Sungai Baru State Elementary School, Gaung District, reached the